Karakteristik Morfofisiologi dan Produksi Bawang Merah Varietas Bima Brebes dengan Pemberian Pupuk Organik Cair pada Sistem Budidaya Terapung - Irmawati, Irmawati; Sefrila, Marlin; Susilawati, Susilawati; Tambunan, Rizky Tadeus; Poerbaputra, Yoszada Dara; Patricya Sinaga, Aulia Putri; Yasyfi Azka Praptawara, Muhammad; Miama Hutabarat, Rahel Valentina; Simanjuntak, Rosita (Seminar Nasional Lahan Suboptimal, 2024)
Irmawati, I., Sefrila, M., Susilawati, S., Tambunan, R. T., Poerbaputra, Y. D., Sinaga, A. P. P., Praptawara, M. Y. A., Hutabarat, R. V. M., Simanjuntak, R. (2024). Morphophysiological characteristics and production of bima brebes shallot variety by providing liquid organic fertilizer in a floating cultivation system. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 202–211).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Shallot cultivation requires the application of technology that is appropriate to the conditions of the agroecosystem plants being planted in order to provide high yields. This research aimed to determine the growth and yield of shallot plants of the Bima Brebes variety which are cultivated using a floating farming system with the addition of liquid organic fertilizer. This research was structured using the Randomized Group Design (RAK) method by carrying out 4 treatment levels, namely P0 = Control (100% NPK), P1 =4 mL L-1POC, P2 = 8 mL L-1 POC, P3 = 16 mL L-1 POC. The results of the diversity analysis showed that the application of liquid organic fertilizer (POC) given to the plants showed that the results were not significantly affected in all growth parameters of the shallot plants. Parameters observed included plant height, number of tillers, number of leaves, level of greenness of leaves, fresh weight of berries, fresh weight of tubers, dry weight of berries, air dried weight of tubers, and tuber diameter. The best leaf length of shallot plants was found in treatment P3 with plant height reaching 32.37 cm. This shows that liquid organic fertilizer can meet the nutrient needs of shallot plants for plant height growth. Research shows that the application of liquid organic fertilizer with treatment at a dose of 16 mL L-1 is able to provide the best results for all parameters of growth and yield of shallot plants.